Minimally Invasive Urology An Essential Clinical Guide to Endourology, Laparoscopy, LESS and Robotics - Best, Sara L.; Nakada, Stephen Y. (Springer New York : Imprint: Springer, 2015)
This volume is an essential and comprehensive review of all aspects of minimally invasive urology. Specifically, the book evaluates minimally invasive approaches to all aspects of clinical urology. Unlike prior texts that focus on a specific technology or a specific disease, this unique reference provides a broad-based view of minimally invasive urology. As such, laparoscopic surgery, robotic surgery, endoscopic surgery, and single-site surgery are all reviewed within the context of renal cancer, renal reconstruction, bladder cancer, prostate cancer, female urology, transplant donor nephrectomy, stone disease, stricture disease, and benign prostatic hyperplasia. The text concludes with chapters on informed consent and cost, which are also quite relevant to the practicing urologist. Authored by a wide array of leaders in the field known for both their clinical prowess and commitment to education, Minimally Invasive Urology: An Essential Clinical Guide to Endourology, Laparoscopy, LESS and Robotics provides a critical resource for clinicians, surgeons, operating room technicians, operating room managers and hospital administration.